Improving the Efficiency of R&D and the Market Diffusion of Energy Technologies - Jochem, Eberhard. (Physica-Verlag HD, 2009)
Is there a chance that public or private research and development institutions can improve the efficiency of the R&D process? This book gives a positive answer by designing an integrated concept of the science technology cycle and the innovation system of each technology. The position of a new technology in the sciencetechnology cycle is identified by several indicators from patent analysis, citations and market information data. The innovation system supports the search for a comprehensive understanding of all important stakeholders of an innovation, possible obstacles and related policies. The application of the methodology leads to convincing results: the hype of the PEM fuel cell activities could have been identified at the end of the 1990s as the phase of euphoria, but not as a situation close to market entry in the car or boiler markets.